Rock Climbing - Carroll, N. (Routledge handbook of strength and conditioning: Sport-specific programming for high performance, 2018)
The chaotic nature of climbing and the rich tradition seen within the sport has meant that for some time there has been little to no formalised strength and conditioning preparation of ath- letes. In recent years the increases in research into the physiological and muscular demands of the sport have started to provide the practitioner with insights into the underlying needs of the sport. Supplementary training away from the wall should aim to promote postural symmetry, increase flexibility around the pelvic girdle, improve lower limb strength and improving upper body strength whilst maintaining a balanced programme given the predominantly pulling bias of the sport. Of interest would be the use of integrated conditioning either by pre-fatiguing the forearm musculature, or by manipulating climbing conditions such as complexity, overhang work and work to rest ratios.